Unravelling the development of regional-scale shear zones by a multidisciplinary approach: The case study of the Ferriere-Mollières Shear Zone (Argentera Massif, Western Alps). (August 2021) - Simonetti, M.; Carosi, R.; Montomoli, C.; Law, R.D.; Cottle, J.M.
Abstract: Shear zone behavior is mainly controlled by deformation regime (brittle versus ductile), deformation temperature, strain rate and magnitude, and rheology of the deformed rocks. If a gradient of strain is established across a shear zone, softening phenomena can produce progressive localization of deformation in its core, resulting in the shear zone maintaining a constant thickness with increasing strain. In contrast, strain hardening processes may induce migration of deformation into the wall-rocks, causing an increase in shear zone thickness. In the Western Alps we have studied a NW-SE striking steeply dipping km-scale shear zone, the Ferriere-Mollières Shear Zone (FMSZ), that cross-cuts Variscan migmatites in the Argentera External Crystalline Massif. The shear zone is characterized by a deformation gradient, with strain increasing toward the center of the shear zone which we interpret to be associated with strain softening during Variscan retrograde metamorphism. In this study, by combining structural and microstructural analyses with quartz fabric analysis, quartz palaeopiezometry and petrochronology, we have identified three main stages of shear zone development, with each stage characterized by specific age, temperature and deformation regime. Stage I occurred between 340 Ma and 330 Ma under a temperature range of 610 - 590 °C with a prevalent (76%–65%) component of pure shear deformation; stage II occurred between 330 and 320 Ma at temperatures between 530 and 480 °C with a decrease in the component of pure shear (73%–49%); stage III developed from 320 to 300 Ma under temperature conditions between 500 and 420 °C with a prevalent component of simple shear (pure shear of 39%–31%). The FMSZ is a new example of a strain-softening and long-lasting regional-scale shear zone, that may prove to be a useful natural study area for future research on processes operating in large-scale shear zones. We argue that the integration of multiple analytical techniques is essential in the study of such regional-scale shear zones and should be regarded as a standard approach.